The Evolution of Energy Deficiency Disorders in Female Athletes: Female Athlete Triad and Relative Energy Deficiency in Sport: Pathophysiology, Diagnosis, and Multidisciplinary Management - a literature review - Bartnik, Katarzyna; Winkowska, Alicja; Pokrzepa, Jakub Jan; Blecharz, Gabriela; Szwech, Julia; Jankowska, Marlena; Hosiawa, Klara; Siewielec, Aleksandra; Mędrysa, Karolina; Chlubek, Anna (Quality in Sport, 2025)
Introduction: The growing participation of female athlethes in competitive and recreational sports has brought attention to sport-specific health concerns related to energy imbalance. The Female Athlete Triad (FAT), characterized by low energy availability (LEA), menstrual dysfunction and low bone mineral density (BMD), and the broader concept of Relative Energy Deficiency in Sport (RED-S) are critical syndromes affecting both health and performance. Purpose: The objective of this review is to examine the current literature on the etiology, pathophysiology, clinical presentation, diagnostic methods, management and prevention of FAT and RED-S in female athletes, with an emphasis on early recognition and interdisciplinary care. Materials and methods: This review is based on a comprehensive literature search conducted on articles sourced from PubMed and Cochrane. The listed keywords were used and analysed for topic relevance and knowledge currency. Conclusion: FAT and RED-S remain underdiagnosed despite significant health risks such as infertility, osteoporosis and reduced performance. Effective prevention and management depend on restoring energy balance that should be supported by a multidisciplinary care team. Continuation of research, education and monitoring are essential to minimize long-term consequences and promote a sport culture that prioritizes both performance and athlete well-being.